Conservation status of the Family Orchidaceae in Mt. Sinaka, Arakan, North Cotabato, Philippines - CHERRY LEE T PANAL; JENNIFER G OPISO; GUILLER OPISO (Biodiversitas Journal of Biological Diversity, 2015)
Panal CLT, Opiso JG, Opiso G. 2015. Conservation status of the Family Orchidaceae in Mt. Sinaka, Arakan, NorthCotabato, Philippines. Biodiversitas 16: 213-224. This study determines the conservation status of the family Orchidaceae, as presenton Mt. Sinaka, Arakan, North Cotabato, Philippines. A thorough survey and alpha taxonomy was done, from base to peak of themountain. Identification of the specimens and assessment of their conservation status was based on the IUCN Red List of ThreatenedPlants 2013.2 and National List of Threatened Philippine Plants of Fernando et al. (2008). Based on the result conducted on October2013-March 2014, out of 59 identified species found in the area, 12 species are widespread, 22 are endemic, 1 vulnerable, 1 criticallyendangered (Paphiopedilum adductum), 1 endangered (Corybas sp.), 2 least concerned species, and 20 unassessed species (not yetassessed by the IUCN). It has been also noted that there are probably some new species, which need thorough study for furtheridentification. The result calls for a desperate need for conservation. Facts from this study helps in addition to the existing wildlifeconservation of flora in Mt. Sinaka and to the other forested mountains in Mindanao, the Philippines.